The Value of Comprehensive Nursing Intervention on Anxiety in Patients with Acute Heart Failure and Diabetes via Expression of Stress-related Genes - Xia, Yingjie; Zhou, Wenhua; Wu, Siyu (Cellular and Molecular Biology, 2022)
Many patients with acute heart failure and diabetes experience varying degrees of anxiety upon entering the cardiac intensive care unit, which has adverse effects on the recovery process of these patients. Anxiety syndrome in these patients increases the risk of death up to three times. This study aimed to determine the effect of comprehensive nursing intervention on anxiety in patients with acute heart failure and diabetes by evaluating the expression of stress-related genes, i.e. COMT and BDNF genes. In this clinical trial study, 74 patients with acute heart failure and diabetes hospitalized in the cardiac intensive care unit were selected by convenience sampling method and randomly assigned to intervention and control groups. The control group received routine ward care, and the intervention group received nursing support program-based interventions in three informational, emotional, and physical dimensions in addition to regular care. Beck Anxiety Inventory was completed before and after the intervention in both groups. The expression of COMT and BDNF genes was evaluated by the qRT-PCR technique. Data were analyzed by Mann-Whitney U and independent T-test in SPSS software version 16. Before the intervention, no significant difference was observed between patients' anxiety scores in the intervention and control groups (p = 0.162). While, after the intervention, the anxiety score of the intervention group was lower than the control group (p = 0.02). The expression of COMT gene results showed that this gene expression was no statistical difference between the control group and intervention group, before intervention (p = 0.83). But, after the intervention, the expression of this gene was statistically decreased in the intervention group in comparison with the control group (p = 0.006). The BDNF gene expression results demonstrated that there was no difference between the two groups, before intervention (p = 0.46). After intervention, statistical increase was observed in control group (p = 0.042) and intervention group (p = 0.007). According to the results of this study, the comprehensive nursing intervention reduced patients' anxiety in the intervention group compared to the control group. This result was also confirmed by evaluating the expression of stress-related genes. Therefore, it is suggested that this intervention method be used to reduce anxiety in these patients.